In a nutshell : cooking and baking with nuts and seeds - Tannenbaum, Cara; Tutunjian, Andrea (W.W. Norton & Company, 2014)
The only cookbook of its kind, In a Nutshell is a complete guide to cooking and baking with nuts and seeds. After working for years as instructors at the Institute of Culinary Education, Cara Tannenbaum and Andrea Tutunjian deliver the essential cookbook for Mother Nature's most versatile and nutritious ingredients. With more than 250 recipes exploring the culinary and cultural history of nuts and seeds in everything from Pumpkin Seed Guacamole to Hazelnut Roulade, In a Nutshell unites the smooth, crunchy, savory, and sweet. In a Nutshell is organized to reflect the way we eat meals today, with chapters like Nibbles, Dip It, Noodles and Nuts, and Family Style. Omnivores, vegetarians, and vegans alike will delight in dishes both simple and complex, from Almond-Crusted Mac-and-Cheese to Pistachio Biryiani. Culinary cheerleaders for the powerful team of sixteen nuts and seeds featured in the book, Tannenbaum and Tutunjian prove that nuts are so much more than a happy-hour snack.